Entrepreneurship Development and Employment in North East India - Sorokhaibam, Robita; Thaimei, Guloulung (Journal of Asian Business Strategy, 2012)
Entrepreneurship development plays a vital role for economic growth and development of a nation or a region within the nation. Out of many important benefits of entrepreneurship development, generation of employments opportunities for job seekers is one of the most important issues. This chapter analyse the relationship between entrepreneurship development and employment in three states that is Assam, Manipur, and Meghalaya.